Allergic rhinitis and associated factors in schoolchildren from Bogota, Colombia (2012)
Allergic rhinitis is one of the most frequent chronic diseases among children. The objective of the study was to assess the prevalence of and the factors associated with self-reported allergic rhinitis symptoms in schoolchildren from Bogota, Colombia. We followed the International Study of Asthma and Allergies in Childhood (ISAAC) methodology. Our sample included 3,256 children aged 6 - 7 and 3,830 adolescents aged 13 - 14 years. The prevalence of self-reported allergic rhinitis symptoms was 30.8% among children and 36.6% among adolescents. Factors associated with self-reported allergic rhinitis among children included current asthma and atopic dermatitis symptoms; use of acetaminophen in the first year of life and in the last 12 months; antibiotic use in the first year of life; high- school and university maternal education; smokers at home; and caesarean delivery. Among adolescents, associated factors included current asthma and atopic dermatitis symptoms; current acetaminophen use once per month; frequent fast-food consumption; cat exposure at home; and smoking. Further exploration of factors associated with allergic rhinitis symptoms is needed.